CSF analysis for protein biomarker identification in patients with leptomeningeal metastases from CNS lymphoma. (3rd April 2017) - Galicia, N.; Dégano, R.; Díez, P.; González-González, M.; Góngora, R.; Ibarrola, N.; Fuentes, M.
ABSTRACT: Introduction : Leptomeningeal metastases (LM) from lymphoma remain a difficult complication for oncologist due to the high incidence in morbidity and mortality. Early diagnostic and initiation of treatment are essential to prevent neurological deterioration. Areas covered : In this review, several proteomic approaches are described in order to help and provide the basis for the identification of biomarkers useful in early diagnosis, also in discovery novel targets for therapeutic agents. In fact, the identification of biomarkers will have a high potential to detect leptomeningeal lymphoma, as well as to predict its progression and treatment response. Expert commentary : In the case of LM by Central nervous system (CNS) lymphoma, these studies generated the first insights into the utility of proteomic analysis for biomarker identification and will be demonstrated that identifying specific proteins in cerebrospinal fluid (CSF) had much greater sensitivity for detecting LM in comparison to standard cytological protocols.